The Quadriptych of Rizq, Ḥabs, Maʿāsh, and ʿUmrān: Insights from Hājar's Statement on Water Rights - Belabes, Abderrazak (Institut Agama Islam Negeri Ponorogo, 2025)
This article explores the meanings underlying Hājar’s statement “you have no right to the water” of Zamzam, based on a philological reading of the original Arabic text mentioned in Ṣaḥīḥ al-Bukhārī. In this respect, it is necessary to understand Hājar’s statement in the general context of the foundation of the Bayt (sacred house), its destruction following Noah's flood, the gushing of Zamzam water, and the rebuilding of the Bayt by Ibrāhīm and Ismāʿīl. From this exploration emerges a quadriptych composed of four key meanings: rizq (divine provision), ḥabs (what is intended for the benefit of everyone), maʿāsh (the world we live from), and ʿumrān (the world we live in). This perspective offers an opportunity to understand Hājar's perception of the interaction between humans and the living milieu beyond the contemporary conceptual language focused on individual ownership. Following her experience of the gushing forth of Zamzam, the human being appears as the steward of God on earth who does not own the goods that he uses. As such, he is supposed to make them bear fruit for his own benefit and that of the community, in harmony with the milieu. The ability to inhabit takes precedence over the ability to appropriate the resources. Focusing on the concept of individual ownership veils the deeper meaning of life that connects the world we live from with the world we live in. Hajar's message is to make choices in favor of life. Such meanings open new avenues for research to go beyond the conceptual frameworks established by Islamic economics and finance, the contemporary jurisprudence of financial transactions, and that of awqāf, embedded in a contract approach centered on individual ownership.